Sociodemographic Determinants, Early Maladaptive Schemas, and Childhood Traumas Increase the Risk of Substance and/or Alcohol Use in Women: A Case–Control Study - Cinar Ozgu; Ergin Isil (Addicta: The Turkish Journal on Addictions)
In this case–control study, to determine the effect of early maladaptive schemas and childhood traumas under risk of alcohol and substance use in women was aimed. The case group of this study consisted of 40 women diag- nosed with alcohol use disorder and/or substance use disorder in Alcohol and Substance Addiction Treatment Centers (AMATEMs) and the control group consisted of 80 women with no diagnosis of alcohol use disorder and/or substance use disorder in Mother and Child Health and Family Planning (ACSAP) Center in a city. Sociodemographic information form, BAPI Alcohol and Substance Scale, Young Schema Questionnaire, and Childhood Trauma Questionnaire were used in study. Chi-square, Mann–Whitney U, Spearman’s correlation tests and logistic regression analysis was used for statistical analysis. According to the results of binary analyses results; being married, having children, living with spouses and children reduce the risk of alcohol or substance use in women; high income, smoking and having alcohol use disorder, or substance use disorder in relatives increase the risk of alcohol or substance use in women. According to the multiple analysis results, smoking is 22.6 fold (CI: 5.58–91.92), relatives substance use disorder 10.3 fold (CI: 1.79–59.73) increases the risk of alcohol or substance use in women. Twelve of 14 schemes and traumas increase the risk of alcohol or substance use in women. Schemas and traumas are risk factors of alcohol or substance use in women.